Progress on the Mechanism of Action of Cornus Officinalis and Its Active Ingredients in the Treatment of Diabetic Nephropathy - Fan, Wenyu; Li, Lianhua (Journal of Contemporary Medical Practice, 2025)
Diabetic nephropathy is a chronic kidney disease caused by diabetes mellitus, which is an important cause of end-stage renal failure and even death in diabetic patients. At present, the main treatment of this disease is basic treatment such as regulating blood glucose, controlling blood pressure, lowering blood lipids, and adjusting the lifestyle, and there is a lack of effective means of prevention and treatment. The Chinese medicine Cornus officinalis has been widely used in the treatment of diabetic nephropathy. The mechanisms involved in the treatment of diabetic nephropathy with Cornus officinalis and its active ingredients include relieving renal vasculopathy, improving renal fibrosis, improving renal filtration function, regulating renal glucose and lipid metabolism, and inhibiting inflammatory response. In this paper, we present a brief review on the mechanism of Cornus officinalis and its active ingredients in the treatment of diabetic nephropathy in recent years, with a view to providing new ideas for clinical and experimental research.